2018
DOI: 10.1093/mnras/sty2184
|View full text |Cite
|
Sign up to set email alerts
|

A Giant Metrewave Radio Telescope survey for associated H i 21 cm absorption in the Caltech–Jodrell flat-spectrum sample

Abstract: We report a Giant Metrewave Radio Telescope (GMRT) survey for associated Hi 21cm absorption from 50 active galactic nuclei (AGNs), at z ≈ 0.04 − 3.01, selected from the Caltech-Jodrell Bank Flat-spectrum (CJF) sample. Clean spectra were obtained towards 40 sources, yielding two new absorption detections, at z = 0.229 towards TXS 0003+380 and z = 0.333 towards TXS 1456+375, besides confirming an earlier detection, at z = 1.277 towards TXS 1543+480. There are 92 CJF sources, at 0.01 z 3.6, with searches for asso… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
41
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 94 publications
5
41
2
Order By: Relevance
“…with detection rates of ∼10-40% in Vermeulen et al 2003;Gupta et al 2006;Chandola et al 2011;Glowacki et al 2017a) and slightly higher than for compact flat spectrum sources (e.g. detection rate of 17% in the Caltech-Jodrell flat-spectrum sample; Aditya & Kanekar 2018). Our detections made towards the GPS sources also support the findings of Maccagni et al (2017), who find a higher Hi detection rate towards compact radio galaxies (32% versus 16% for the extended sources within their sample).…”
Section: Hi Detections In Gps Sourcessupporting
confidence: 87%
“…with detection rates of ∼10-40% in Vermeulen et al 2003;Gupta et al 2006;Chandola et al 2011;Glowacki et al 2017a) and slightly higher than for compact flat spectrum sources (e.g. detection rate of 17% in the Caltech-Jodrell flat-spectrum sample; Aditya & Kanekar 2018). Our detections made towards the GPS sources also support the findings of Maccagni et al (2017), who find a higher Hi detection rate towards compact radio galaxies (32% versus 16% for the extended sources within their sample).…”
Section: Hi Detections In Gps Sourcessupporting
confidence: 87%
“…In particular, there is a factor of ∼ 6 discrepancy between the detection rates in nearby objects and those at higher redshifts (e.g. Curran et al 2008;Curran & Whiting 2010Aditya et al 2016;Aditya & Kanekar 2018;Curran et al 2019;Grasha et al 2019). The lower detection rates of intrinsic absorbers in highredshift objects are thought to be due to selection bias -from either UV-luminous quasars that ionize the gas or excitation of the gas by 21-cm photons from the radio source -and possibly also intrinsic redshift evolution in the host galaxy population.…”
Section: Intrinsic 21-cm Absorbersmentioning
confidence: 99%
“…The sample of Maccagni et al (2017) spanned comparatively lower luminosities between L 1.4 = 3.2 × 10 22 and 1.6 × 10 26 W Hz −1 , indicating that there could be a bias. However, Aditya & Kanekar (2018) 1.2) compact flat-spectrum radio sources with max-imum radio luminosity max(L 1.4 ) = 5.0 × 10 27 W Hz −1 . Furthermore, in their targeted survey of 145 compact radio sources, spanning luminosities in the range L 1.4 = 1.6 × 10 25 and 4.5 × 10 28 W Hz −1 , Grasha et al (2019) found no evidence for a statistical correlation between their detection rate and radio luminosity.…”
Section: Intrinsic 21-cm Absorbersmentioning
confidence: 99%
“…Overall, at present over 650 systems have been searched for associated Hi 21-cm absorption (e.g., Vermeulen et al 2003;Gupta et al 2006;Curran et al 2013;Aditya et al 2016;Maccagni et al 2017;Aditya & Kanekar 2018b), with more than 120 detections reported in the literature. A majority ( 550) of the searches have been limited to redshifts z < 0.6, that consist of samples of both compact, flat-to-inverted spectrum sources and extended, steepspectrum radio sources.…”
Section: Introductionmentioning
confidence: 99%
“…At redshifts z > 1.0, however, compact, flat-spectrum radio sources dominate the samples that have been searched for associated Hi 21-cm absorption. Approximately 90 sources have been searched at z > 1.0 (e.g., Curran et al 2013;Aditya et al 2016;Aditya & Kanekar 2018b) with the detection rate being consistently low at 10% (compared to ∼ 30% at low-z -cf. Geréb et al 2015 ).…”
Section: Introductionmentioning
confidence: 99%